2022
DOI: 10.1111/nmo.14502
|View full text |Cite
|
Sign up to set email alerts
|

Is the Sars‐CoV‐2 virus a possible trigger agent for the development of achalasia?

Abstract: Background Achalasia is an autoimmune disease whose probable causal agent is a neurotropic virus that chronically infects the myenteric plexus of the esophagus and induces the disease in a genetically susceptible host. The association between achalasia and coronaviruses has not been reported. Aims To evaluate the presence of the SARS‐CoV‐2 virus, the ACE2 expression, the tissue architecture, and immune response in the lower esophageal sphincter muscle (LESm) of achalasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The evidence of achalasia linked to the COVID-19 infection, however, is relatively limited. Our literature review, as presented in ▶ Table 1, identified a small number of similar cases that have been reported in recent years [24,25,26,27,28]. Despite these case reports, collectively, the evidence is sparse and the interventions and outcomes varied, reinforcing the necessity for more extensive research.…”
Section: Discussionmentioning
confidence: 93%
“…The evidence of achalasia linked to the COVID-19 infection, however, is relatively limited. Our literature review, as presented in ▶ Table 1, identified a small number of similar cases that have been reported in recent years [24,25,26,27,28]. Despite these case reports, collectively, the evidence is sparse and the interventions and outcomes varied, reinforcing the necessity for more extensive research.…”
Section: Discussionmentioning
confidence: 93%
“…It is therefore possible that SARS-CoV-2, with an affinity for neuronally expressed ACE2 receptors (12), is similarly triggering an inflammatory process resulting in ganglionic cell destruction within the esophagus and subsequently leading to achalasia. In fact, a recent study reported a lower number of regulatory lymphocytes in esophageal muscle in achalasia with SARS-CoV-2 (6), which could be associated with more severe and prolonged inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the virus responsible for coronavirus disease 2019 (COVID-19), has been associated with various transient gastrointestinal (GI) manifestations (3,4) including a report of autoimmune GI dysmotility (5). A recent report examining presence of SARS-CoV-2 in esophageal muscle tissue at the time of Heller myotomy reported a case of achalasia that developed after COVID-19 (6). Since 2020, we observed several cases of type 2 achalasia in previously asymptomatic young to middle-aged patients shortly after SARS-CoV-2 infections at 3 medical centers.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Furuzawa-Carballeda and colleagues discovered SARS-CoV-2 and its receptor in the lower-oesophageal-sphincter (LOS) muscle complex of achalasia patients who had COVID-19, but not in achalasia patients without COVID-19 or controls. This study postulated that the presence of the SARS-CoV-2 virus in the LOS may be associated with the development of post-COVID-19 achalasia [ 120 ]. Furthermore, the association between SARS-CoV-2 infection and ileocolic intussusception has been postulated; a recent report revealed the presence of the virus in the mesenteric lymph node and the ileum of the infected children [ 121 ].…”
Section: Pathogens and Ens Development And Diseasementioning
confidence: 99%